The role of ABI3 in human induced pluripotent stem cell‐derived microglia: Developing topics. (7th December 2020) - Rolova, Taisia; Zhang, Fuping; Koskuvi, Marja; Koistinaho, Jari
Abstract: Background: Microglia are the main immune cells of the central nervous system clearing invaded pathogens, damaged cells and toxic aggregates, thus maintaining tissue homeostasis. However, in Alzheimer's disease (AD), microglia do not perform their job that well anymore. Recent genome‐wide association studies (GWAS) have strongly implicated microglia in AD pathogenesis. One of the genetic variants recently identified is rs616338/p.S209F in ABI3 gene (OR 1.43), which is stronger expressed in microglia than other types of brain cells. ABI3 (ABI family member 3) is a structural component of WAVE2 complex known to regulate formation of lamellipodia, membrane ruffling and phagocytosis. However, the role of ABI3 and its functional difference from a similar protein ABI1 in microglia is not clear. Method: We have used CRISPR/Cas9 technique to generate a knockout iPS line (ABI3 KO) producing truncated protein that lacks Src‐homology 3 domain crucial for the regulation of actin remodeling. We have further differentiated ABI3 KO line and the original isogenic control line (WT) into microglia according to the previously published protocol of McQuade et al (2018). Result: We have found that ABI3 KO microglia exhibited significantly lower uptake of zymosan‐conjugated pHrodo beads, lower expression level of scavenger receptor MSR1 and higher expression level of glucose transporter SLC2A1 as compared to the WT control. ABI3 KO cells were also significantly less responsive to ADP in Transwell migration assay although the mRNA expression of P2RY12 receptor was higher in the KO cells. The protein level of WAVE2 was similar but the level of ABI1 was strongly increased in ABI3 KO cells suggesting a compensatory effect. ABI3 deficiency did not significantly affect secretion of Aβ42, phosphorylation of TAU at Ser214 and phosphorylation of APP at Thr668 in co‐culture with human iPS‐derived neurons harboring Swedish mutation in APP. Conclusion: In conclusion, ABI3 deficiency in microglia significantly impaired phagocytosis and ADP‐induced migration but did not have an effect on AD‐like pathology in co‐culture with diseased iPS‐derived neurons.